CHANGES IN CORNEAL BIOMECHANICS AFTER REFRACTIVE SURGERY USING CORVIS ST - A QUASI EXPERIMENTAL STUDY - Younis, Fazla; Zafar, Omar; Basit, Imran; Jabeen, Fatima (Pakistan Armed Forces Medical Journal, 2020)
Objective: To assess the corneal biomechanical changes after refractive surgery using Corvis ST (Oculus Wetzlar, Germany) a dynamic scheimpflug analyzer. Study Design: Quasi experimental study. Place and Duration of Study: The study was conducted at Armed Forces Institute of Ophthalmology (AFIO), Rawalpindi, from Feb 2019 to Jul 2019. Methodology: Following strict inclusion criteria 32 patients were recruited in the study. Total of 64 eyes of patients underwent refractive surgery. Laser in situ keratomileusis (LASIK) was performed on 44 eyes and Photorefractive keratectomy (PRK) was performed on 20 eyes. All measurements for assessment of corneal biomechanics generated by Corvis ST were taken before surgery, 1 week and one month after the procedure with scheimpflug based device (Corvis ST, oculus). Results: In LASIK surgery after a week there was a change in pachymetry, A1 length, radius and IOP and at one-month pachymetry, deformation amplitude, A1 time, A1 length, A2 length, radius, Intraocular pressure (IOP) and peak distance came out statistically significant with a p-value of <0.05. In PRK group Pachymetry, A1 length and radius were statistically significant (p-value <0.05) after a month with no difference in parameters after one week. Conclusion: Our study concluded that there were modifications in biomechanical parameters after LASIK and PRK, indicating changes in cornea after refractive procedures with PRK being less aggressive than Lasik.